1994
DOI: 10.1111/j.1365-2362.1994.tb02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of haemodynamic changes after maximal exercise

Abstract: The haemodynamic changes during 4 h following maximal upright bicycle exercise were evaluated in six normals in a randomized controlled crossover design. Total peripheral resistance was reduced to 2 h (-6.7 mmHg min l-1, P < 0.05); exercising and non-exercising vascular beds were vasodilated for 2 h (-24.1 and -23.8 mmHg min ml-1 100 ml-1 tissue, respectively, P < 0.05), associated with reductions in systolic (-5.8 mmHg, P < 0.05) and diastolic pressure (-8.3 mmHg, P < 0.05). Rise in cardiac index for 1 h (+0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…A number of studies have found decreased peripheral resistance at sites other than those of the exercising muscle, suggesting that the reduction is a whole body phenomenon. 22,35,43 However, Hagberg et al 13 found increases in total peripheral resistance in older…”
Section: Peripheral Resistancementioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies have found decreased peripheral resistance at sites other than those of the exercising muscle, suggesting that the reduction is a whole body phenomenon. 22,35,43 However, Hagberg et al 13 found increases in total peripheral resistance in older…”
Section: Peripheral Resistancementioning
confidence: 99%
“…In those studies that have observed a decline in blood pressure following exercise, the average decrement in pressure was approximately 8/9 (SBP/DBP) mm Hg in the normotensive population, 16,[20][21][22][23]25,[31][32][33][34][35] 14/9 mm Hg in the borderline hypertensive population [10][11][12]34,[36][37][38][39] and 10/7 mm Hg in the hypertensive population. 13 37 We recently examined the effects of the exercising muscle mass by comparing the PEH response to both leg and arm ergometry at the same relative intensity.…”
Section: Magnitude Of the Blood Pressure Declinementioning
confidence: 99%
See 3 more Smart Citations